2010
DOI: 10.1166/jnn.2010.2333
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Sensor Based on Porous Silicon Dual Transducers

Abstract: Novel porous Si exhibiting dual optical properties, both Fabry-Perot fringe (optical reflectivity) and photoluminescence, were developed and used as chemical sensors. Porous Si samples were prepared by an electrochemical etch of p-type silicon under the illumination with a 300 W tungsten filament bulb for the duration of etch. The surface of porous Si was characterized by FT-IR instrument. The porosity of samples was about 80%. Both reflectivity and photoluminescence were simultaneously measured under the expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The PL efficiency of PSi relies on the interior diverse structures and the versatile surface properties [ 15 ]. Organic vapors have been detected by PL quenching due to the differences in the physicochemical properties between the organic molecules [ 16 ]. Here, we report a method for the preparation of photoluminescent rugate PSi exhibiting both well reflection and PL based on highly doped n-type silicon wafers.…”
Section: Introductionmentioning
confidence: 99%
“…The PL efficiency of PSi relies on the interior diverse structures and the versatile surface properties [ 15 ]. Organic vapors have been detected by PL quenching due to the differences in the physicochemical properties between the organic molecules [ 16 ]. Here, we report a method for the preparation of photoluminescent rugate PSi exhibiting both well reflection and PL based on highly doped n-type silicon wafers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, PS samples exhibiting both strong PL and well defined Fabry-Pérot fringes or Bragg reflections were reported. Both PL and reflectivity of PS were used to detect organic vapors [11] and nerve agent simulants [12].…”
Section: Introductionmentioning
confidence: 99%
“…16 Organic vapors have been detected quantitatively by quenching of photoluminescence of the quantum-confined silicon crystallites in PS. 17 However, many researches indicated that the oxidation of silicon nanoparticles or silicon quantum dots (Si QDs) causes the degradation of their luminescence. 18 Oxidation mechanism of Si-Si bond is reported previously.…”
Section: Introductionmentioning
confidence: 99%